THE PRICE OF OIL. REACHING FOR THE BOTTOM - VADIM VITAL’EVICH Ponkratov (Мир новой экономики, 2018)
The article is devoted to the dynamics assessment of oil prices since mid-2014 and the analysis of its determinants. It has been established that the cause of the current oil crisis was the continuing overproduction of oil, due to near-zero growth of the world economy and the market entry of a large numberof non-conventional hydrocarbon reserves, production of which has become profitable thanks to the ultra-high oil prices in 2006-2013. Taken together, this has led to a change in the landscape of the oil market and revealed the reluctance of member countries of OPEC to influence the price levels by reducing the supplyof oil for the fear of losing their market share. Prepared is the medium term forecast of oil prices dynamics according to the analysis of factors that determine it.